Sensory Habituation as a Shared Mechanism for Sensory Over-Responsivity and Obsessive–Compulsive Symptoms - Podoly, Tamar Y.; Ben-Sasson, Ayelet (Frontiers in Integrative Neuroscience, 2020)
Abstract Background: Some individuals who suffer from Obsessive Compulsive Disorder (OCD), report disturbing sensory preoccupations. The inability to stop obsessing over stimuli resonates with a difficulty in sensory habituation. Impaired sensory habituation, to a degree that clearly dysregulates response to sensory stimuli, and impairs participation in everyday activities, can be part of a disorder known as Sensory Over-Responsivity (SOR). Although previous studies indicated a correlation between OCD and SOR, physiological experiments show that individuals with OCD are not more sensitive to sensory stimuli than controls. In the current study we (1) validated a sensory habituation psycho-physiological protocol and (2) tested whether a ‘slow to habituate’ mechanism can explain the occurrence of elevated SOR and OC symptoms. Method: We designed a protocol to test auditory sensory habituation through Electro Dermal Activity (EDA) recording. The protocol included two randomly ordered aversive and neutral sound conditions, each set of 6 everyday life sounds was presented as a continuous stimulus. During the presentation of sounds, EDA was measured and participants could press a button to shorten the stimuli. Participants also completed sensory and OC symptom questionnaires. Participants included 100 typically developing adults that were divided into high versus low OC symptom groups. Mixed models analysis was used throughout to meet the need for capturing the temporal nature of habituation. Results: Distinct physiological indices were computed to measure sensitivity versus habituation. Habituation was slower in the aversive versus neutral condition. Sensitivity was higher for the aversive stimuli. Self-report of sensory habituation and sensitivity partially correlated with the physiological habituation indices. A comparison of the physiological pattern between those with high versus low OC symptoms revealed significant differences in the habituation and sensitivity indices, across conditions. Conclusions: The interplay between SOR and OC symptoms can be explained by A ‘slow to habituate’ mechanism. Identifying behavioral and physiological markers of sensory problems in OCD is important for assessment, intervention and the discovery of underlying mechanisms.